Effects of Sevoflurane and Halothane on Haemodynamics During Induction of General Anaesthesia using Laryngeal Mask Airway in Children - Shrestha, Asmita; Amatya, Bishwo Ram; Gautam, Alok Raj; Panta, Sunita (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Inhalational anaesthesia is a preferred technique of induction in children. Halothane has been commonly used for inhalational induction. Sevoflurane with low blood gas solubility and pleasant odor allows rapid induction, early and smooth emergence. The study was conducted to observe effects of sevoflurane and halothane on hemodynamics during induction of general anaesthesia using laryngeal mask airway in children. Methods: This prospective, observational study was conducted among 60 ASA PS I children aged 2 - 12 years. The two groups of children undergoing surgery with halothane and sevoflurane induction were compared. Heart rate, mean arterial pressure and complications were observed between two groups. Results: The two groups were comparable in terms of age, weight, sex distribution, ASA status and surgical procedure. There was no significant difference in heart rate and mean arterial pressure during pre - induction, loss of eyelash reflex, immediately after LMA insertion and then 3 mins and 5 mins later. There were two cases of arrhythmia in halothane group and two cases of laryngospasm in sevoflurane group. Conclusions: There was no significant difference in effects of sevoflurane and halothane on hemodynamics during induction of general anaesthesia using LMA in paediatric patients. Hence, both agents can be safely used.